Biological activity of Passiflora edulis f. Flavicarpa ethanolic leaves extract on human colonic adenocarcinoma cells (2019)
ABSTRACT: Studies of extracts and phytochemicals from Passiflora genus have shown promissory biological activity for cancer chemoprevention; thus, in this work, it was evaluated the anticancer potential of the ethanolic extract of Passiflora edulis f. Flavicarpa leaves over Caco-2 and SW480 colorectal adenocarcinoma cells. The effect of the extract on cell viability was evaluated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide and its antiproliferative activity was assessed by clonogenic assays. In addition, by flow cytometry approaches, it was evaluated the apoptosis-inducing effect and cell cycle regulation. In this way, it was established the half maximal inhibitory concentration (IC50) of the extract over both cell lines and also, it was observed the inhibition of cellular proliferation after 48 hours of exposure to the extract. On the other hand, we observed that the extract induced cell death-mechanisms, by the increasing of the proportion of necrotic and apoptotic cells; furthermore, the extract altered the distribution of cell cycle phases by increasing SubG1 and G2/M populations. Altogether, these results suggest that P. edulis is a potential source of phytochemical compounds with anticancer properties for the management of colorectal cancer patients.